THE MAPPING OF UNIVERSITY STUDENT’S BACKGROUND, EXPECTATION, AND ENTREPRENEURSHIP VIEW ON FUTURE CAREER - S Sunarni (Faculty of Education Universitas Negeri Malang, 2018)
This research aims at: 1) mapping university student’s background, 2) expectation university students on future career, 3) finding out the differences of student’s background and expectation. This research uses descriptive comparative method. The population of this research is students of AP FIP UM and MP FIP UNESA. The number of sample is 248 respondents from 743 populations. Data is taken using questionnaire. The results are: 1) most students are from East Java and graduated from Senior High School. The parents’ highest educations are from Senior High School. Parents’ occupation is businessmen. Students’ interest is art. Most parent’s expectation that their children will reach career as public servant (PNS). 2) Students college after graduation, they have expectation to work in the field of education on the staff of the Ministry of National Education. Non-educational field, they have hopes to be an employee of Bank. 3) Based on group variable university, sex, and student year, there are similarities and there are differences. Keywords: mapping students’ background, expectation, future career, entrepreneurship